2012
DOI: 10.1183/09031936.00194611
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and effect on biomarkers of AZD9668 in cystic fibrosis

Abstract: The aim of this study was to evaluate the safety and effect on clinical outcomes and biomarkers of inflammation and tissue damage of the neutrophil elastase inhibitor AZD9668 (60 mg twice daily orally for 4 weeks) in cystic fibrosis.This was a randomised, double-blind, placebo-controlled study. Primary outcome measures were sputum neutrophil count, lung function, 24-h sputum weight, BronkoTest1 diary card data and health-related quality-of-life (revised cystic fibrosis quality-of-life questionnaire). Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 34 publications
4
54
0
Order By: Relevance
“…The antiinflammatory properties of neutrophil elastase inhibitors are well established, 26 and at least one such agent has shown promise in early trials involving adults with cystic fibrosis. 24 In conclusion, free neutrophil elastase activity in the lung at 3 months of age was associated with increased odds of persistent bronchiectasis at 12 months and at 3 years of age. This observation sets the stage for trials of treatments that target activated neutrophils or inhibit neutrophil elastase activity in order to prevent or delay the onset of bronchiectasis in patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiinflammatory properties of neutrophil elastase inhibitors are well established, 26 and at least one such agent has shown promise in early trials involving adults with cystic fibrosis. 24 In conclusion, free neutrophil elastase activity in the lung at 3 months of age was associated with increased odds of persistent bronchiectasis at 12 months and at 3 years of age. This observation sets the stage for trials of treatments that target activated neutrophils or inhibit neutrophil elastase activity in order to prevent or delay the onset of bronchiectasis in patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such therapies are available or are under investigation in clinical trials, [24][25][26] highlighting the relevance of understanding the role that neutrophil elastase may play in disease initiation and progression. Studies of ibuprofen in older children and adults have shown a delayed decrease in lung function and improved maintenance of weight, with these findings attributed to antiinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is not known; it might be surmised and speculated that AZD9668 (13) is not sufficiently stable, e.g., under sustained oxidative stress conditions. 68 Based on these data, a dose of 60 mg b.i.d. AZD9668 (13) has been orally administered to assess safety and efficacy in CF, BE, and COPD patients.…”
Section: Nd Generation (Mechanism-based Suicide Smols) Along the Linmentioning
confidence: 99%
“…The potential to reduce proteolytic lung damage through the use of synthetic NE inhibitors has also been explored. However, the lack of clinical benefit in usual COPD [93] and other conditions such as cystic fibrosis [94] and acute lung injury [95] have meant that trials in A1ATD have not been undertaken.…”
Section: Treatment Of A1at-related Copdmentioning
confidence: 99%